Autocatalytic Metallization of Fabrics Using Si Ink, for Biosensors, Batteries and Energy Harvesting. (9th November 2018) - Grell, Max; Dincer, Can; Le, Thao; Lauri, Alberto; Nunez Bajo, Estefania; Kasimatis, Michael; Barandun, Giandrin; Maier, Stefan A.; Cass, Anthony E. G.; Güder, Firat
Abstract: Commercially available metal inks are mainly designed for planar substrates (for example, polyethylene terephthalate foils or ceramics), and they contain hydrophobic polymer binders that fill the pores in fabrics when printed, thus resulting in hydrophobic electrodes. Here, a low‐cost binder‐free method for the metallization of woven and nonwoven fabrics is presented that preserves the 3D structure and hydrophilicity of the substrate. Metals such as Au, Ag, and Pt are grown autocatalytically, using metal salts, inside the fibrous network of fabrics at room temperature in a two‐step process, with a water‐based silicon particle ink acting as precursor. Using this method, (patterned) metallized fabrics are being enabled to be produced with low electrical resistance (less than 3.5 Ω sq −1 ). In addition to fabrics, the method is also compatible with other 3D hydrophilic substrates such as nitrocellulose membranes. The versatility of this method is demonstrated by producing coil antennas for wireless energy harvesting, Ag–Zn batteries for energy storage, electrochemical biosensors for the detection of DNA/proteins, and as a substrate for optical sensing by surface enhanced Raman spectroscopy. In the future, this method of metallization may pave the way for new classes of high‐performance devices using low‐cost fabrics. Abstract : Hydrophilic metallization on fabrics for new high‐performance devices is demonstrated. A wide range of metals are deposited inside fabrics (paper, cotton) and nitrocellulose membranes, without modifying the surface. Coil antennas are then demonstrated for wireless energy harvesting, Ag–Zn batteries for energy storage, electrochemical biosensors for DNA/protein detection, and a substrate for surface enhanced Raman spectroscopy.